Handbook of Children and the Media - Singer, Dorothy G.; Singer, Jerome L. (Thousand Oaks, Calif. : Sage Publications, 2001)
From Internet censorship to levels of television exposure, the effects of mass media on children is one of the most widely debated issues in our society. Bringing together an interdisciplinary group of scholars from around the world, the Handbook of Children and the Media is a comprehensive analysis of the field for students and scholars. This book summarizes the current scope of research on children and the media, suggests directions for future research, and attempts to provide students with a deliberate examination of how children use, enjoy, learn from, and are advantaged or disadvantaged by regular exposure to television and other electronic media. --From publisher's description.
Part I. The popular media as educators and socializers of growing children -- The history of children's use of electronic media / Haejung Paik -- Free reading : implications for child development / Roger Desmond -- The use of television and other film-related media / George Comstock, Erica Scharrer -- New forms of electronic media : the impact of interactive games and the Internet on cognition, socialization, and behavior / Kaveri Subrahmanyam -- Attention, comprehension, and the educational influences of television / David S. Bickham, John C. Wright, Aletha C. Huston -- Television and the child's developing imagination / Patti M. Valkenburg -- Television as incidental language teacher / Letitia R. Naigles, Lara Mayeux -- Creating vigilance for better learning from television / Dorina Miron, Jennings Bryant, Dolf Zillmann -- Prosocial effects on children's social interactions / Marie-Louise Mares, Emory H. Woodard -- The media and children's fears, anxieties, and perceptions of danger / Joanne Cantor -- Effects of televised violence on aggression / Brad J. Bushman, L. Rowell Huesmann -- Media violence in cross-cultural perspective : a global study on children's media behavior and some educational implications / Jo Groebel -- Research on sex in the media : what do we know about effects on children and adolescents? / Neil M. Malamuth, Emily A. Impett -- Sex in the media : theory, influences, and solutions / Ed Donnerstein, Stacy Smith -- Mass media and identity development / Nina Huntemann, Michael Morgan -- Media and the family / Robert Kubey, Barna William Donovan -- Television's gender role images and contribution to stereotyping : past, present, future / Nancy Signorielli -- Television, children, and multicultural awareness : comprehending the medium in a complex multimedia society / Gordon L. Berry, Joy Keiko Asamen -- Children and television advertising / Dale Kunkel -- Popular music in childhood and adolescence / Donald F. Roberts, Peter G. Christenson -- Children, adolescents, drugs, and the media / Victor C. Strasburger -- Television food advertising : targeting children in a toxic environment / Katherine Battle Horgen, Molly Choate, Kelly D. Brownell -- Television and morality / Lawrence I. Rosenkoetter -- Part II. Forging the media environment for the future : the media industry and its technology -- The economic structure of the commercial electronic children's media industries / J. Cory Allen -- Broadcast networks and the children's television business / Alison Alexander -- Serving the very young and the restless : children's programming on public television / Jerry Franklin, Larry Rifkin, Patrice Pascual -- PRIX JEUNESSE as a force for cultural diversity / David W. Kleeman -- Cable television : gateway to educational resources for development at all ages / Peter J. Dirr -- Children, the Internet, and other new technologies / Todd Tarpley -- Hazards and possibilities of commercial TV in the schools / Ellen Wartella, Nancy Jennings -- The role of research in educational television / Michael Cohen -- Part III. Policy issues and advocacy -- Children and media policy / Dale Kunkel, Brian Wilcox -- Industry standards and practices : compliance with the Children's Television Act / Karen Hill-Scott -- Child and parent responses to the age-based and content-based television ratings / Bradley S. Greenberg, Lynn Rampoldi-Hnilo -- Digital kids : the new on-line children's consumer culture / Kathryn C. Montgomery -- Public policy and private practice : government regulations and parental control of children's television use in the home / Amy B. Jordan -- Parents and other adults : models and monitors of healthy media habits / Marjorie J. Hogan -- Media literacy and critical television viewing in education / James A. Brown -- Children's advocacy groups : a history and analysis / Laurie Trotta.
Includes bibliographical references and index.
Keywords: Television and children -- United States; Mass media and children -- United States; Video games -- Psychological aspects; Television; Advertising as Topic; Child; Psychology, Child; Internet; Video Games -- psychology; United States